Combined Transcriptome Analysis Reveals the Mechanism of ‘Shine Muscat’ Pollen Abortion Induced by CPPU and TDZ Treatment - Mengfan Ren; Yixu Wang; Siyi Yi; Jingyi Chen; Wen Zhang; Haoran Li; Ke Du; Jianmin Tao; Huan Zheng (Horticulturae)
N-(2-chloro-4-pyridyl)-N′-phenylurea (CPPU) and N-phenyl-1,2,3-thidiazole-5ylurea (TDZ) are plant growth regulators used for seedless treatment in grape. In this study, the flowers of ‘Shine Muscat’ (Vitis labruscana Bailey × V. vinifera L.) were treated with 3, 5, and 10 mg/L CPPU and TDZ one week before flowering. The results showed that both CPPU and TDZ treatments reduced the pollen germination rate and caused abnormal stamen and pollen grain phenotypes, resembling the male sterility observed in ‘Y_14’ (a novel grapevine germplasm derived from the self-progeny of ‘Shine Muscat’). Using RNA-seq technology, the stamens of flowers treated with 10 mg/L CPPU (CPPU_10), 10 mg/L TDZ (TDZ_10), and the control (CK) were analyzed. A total of 520 and 722 differentially expressed genes (DEGs) were identified in CPPU and TDZ treatments, respectively. GO and KEGG analyses revealed that the common pathways leading to pollen abortion in both treatments were primarily associated with hydrolase activity (acting on glycosyl bonds), phenylpropanoid biosynthesis, pentose and glucuronate interconversions, and ABC transporters. By comparing the DEGs across the three groups (Y_14 vs. SM, CPPU_10 vs. CK, TDZ_10 vs. CK), 16 DEGs exhibited similar expression patterns. Further tissue-specific expression analysis identified nine genes that were highly expressed in stamens and shared the same expression pattern in sterile lines. These findings provide a foundation for further studies on the impact of CPPU and TDZ treatments on grape stamen fertility.